2019
DOI: 10.17584/rcch.2019v13i2.8987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trans-zeatin riboside application on growth of banana (Musa AAA Simmonds) cv. Williams in the juvenile phase

Abstract: Cytokinins are physiologically active adenine derivatives that are vital to the regulation of various developmental processes in plants, such as vegetative growth and flower induction. The objective of this study was to understand how the application of cytokinin trans-zeatin riboside affects growth in banana (Musa AAA Simmonds) cv. Williams plants during the vegetative phase on two farms located in the production zone of the Magdalena province, Colombia. The effect of trans-zeatin riboside applications at dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…In detail, GA 4+7 at a high concentration and GA 3 at a low concentration have the best effects (Tables 1 and 3). Zeatin and its derivatives occur in many plant extracts and are the active ingredient in coconut milk, which causes plant growth [38]; applications of zeatin riboside stimulated cell growth (cell division or/and cell elongation) in banana fruit [39]. Our data also showed that it has a fruit-prompting function (Table 1).…”
Section: Discussionsupporting
confidence: 65%
“…In detail, GA 4+7 at a high concentration and GA 3 at a low concentration have the best effects (Tables 1 and 3). Zeatin and its derivatives occur in many plant extracts and are the active ingredient in coconut milk, which causes plant growth [38]; applications of zeatin riboside stimulated cell growth (cell division or/and cell elongation) in banana fruit [39]. Our data also showed that it has a fruit-prompting function (Table 1).…”
Section: Discussionsupporting
confidence: 65%